Design of modular autoproteolytic gene switches responsive to anti-coronavirus drug candidates - Nik Franko (Nature Portfolio, 2021)
SARS-CoV-2 proteases are key targets for anti-viral drug development. Here the authors present modular tunable autoproteolytic gene switches for virus free cell culture screening of inhibitors.